Fire resistance evaluation for the steel roof structure of a typical warehouse. - Panedpojaman, Pattamad
The fire resistance of the steel roof structure of a typical warehouse is investigated in the current study. Various fire scenarios are simulated using the Fire Dynamics Simulator (FDS) program. The simulation considers the fuel type and the clearance height of the warehouse as the varying parameters. The fire modeling results demonstrate that the fuel types significantly affect the behavior of the modeled fire in terms of the fire growth and the spread of flames. For each of the modeled fire scenarios, the behavior of the roof structure is examined using nonlinear structural analysis, taking into account the varying properties of steel under fire, with and without fire protection. It has been found that the failure time of the roof structure depends upon the fuel type and whether or not the roof members are protected from fire and that the fire resistance of protection for structural steel sections based on ASTM E 119 may not be conservative.
Keywords: Failure time; Fire modeling; Fire resistance; Roof structure; Structural analysis